Community participation in tourism planning at Majete Wildlife Reserve, Malawi. - Bello, Felix G. (Quaestiones Geographicae, 2021)
This research assessed the local community’s participation in protected area-based tourism planning at Majete Wildlife Reserve in Malawi. The assessment was based on the participatory planning elements from the community participation framework for protected area-based tourism planning. A qualitative research approach was applied, and both secondary and primary data sources were used. Content analysis was used to analyse the data. Results show that the reserve has a system that allows continuous local community participation in the planning process, with financial resources committed to support the process. Local people are represented by independent community-based organisations and traditional leaders during the planning processes. But the local communities have limited access to tourism information and tourism planning experts. The reserve also lacks an appropriate decision-making structure that can facilitate efficient flow of management decisions to local communities. There is need to empower local people and regard them as partners in the tourism planning processes so that they can influence decisions.